ASD and offending: reflections of practice in from a New Zealand perspective. Issue 2 (12th June 2017) - Bathgate, David
Abstract : Purpose: There is growing awareness in New Zealand (NZ) of the impact that Autistic Spectrum Disorder (ASD) has on individuals and their families and the ability to engage in health services. Although it is a relatively rare condition, approximately 1 per cent of the population will have ASD, directly affecting approximately 40, 000 individuals in NZ. The purpose of this paper is to provide some reflections and questions on what we can learn from a NZ perspective. This is based on an overview of the limited literature around ASD and offending and the author's experience in the UK working in a medium secure unit. Design/methodology/approach: Through a past site visit as part of the annual international conference on the Care and Treatment of Offenders with an Intellectual and/or Developmental Disability in the United Kingdom (UK), the author became aware of the medium secure forensic unit for male patients with ASD at the Roseberry Park Hospital (UK's Tees, Esk and Wear Valleys NHS Foundation Trust). During the author's advanced training in forensic psychiatry with the Royal Australian and New Zealand College of Psychiatrists the author was privileged to be able to apply and be accepted for a four-month sabbatical training position at this hospital. Findings: Outlined is background information about ASD and review findings from the limited literature on ASD and offending. Also outlined is the author's learning as a trainee working in medium secure unit for people with ASD who have offended, and finally how this experience may help in the development of services in NZ, given that at this stage such services are under-developed. Originality/value: To be able to share the valuable experience and learning opportunity the author was able to have, as well as raise the awareness of ASD generally, and specifically the need for specialist services for the small number of people with ASD who come into contact with Justice Services.